AN ANALYSIS OF ENGLISH-SPEAKING ACTIVITY FOR INTROVERT LEARNERS’ NECESSITY - Asih, Femmy Kurnia; Jaya, Aswadi; Theriana, Ana; Hermansyah, Hermansyah (English Community Journal, 2021)
This study focuses on introvert learners in eighth grader of A and B class. Totaling 72 students and 2 teachers at state Junior High School 2 Sungailiat. The objective of this study is to determine the lack and expectation of introvert learners and the teacher of English handles introvert learners for the importance of their speaking ability. This study used descriptive study and used questionnaire to analyze students who are classified as introvert and interviewed with teacher of English and counseling teacher. The result that 8 introvert learners in eighth grader of A and B class. The biggest problems faced by introvert learners were lack of vocabulary and self-confidence in their speaking activities. Introvert learners found it difficult to express opinions in front of many people. Then, teacher of English could provide learning based on the lack of introvert learners, such as group discussion, thus introvert learners could express their opinions in a small scope. The expectation of introvert learners, was that teacher of English paid more attention to themselves. The teacher could provide material with the media of English songs because introvert learners tend to be audio-visual learners, introvert learners more easily accept the material in a fun way.